FAKTOR-FAKTOR ANTESEDEN PENENTU KEPUASAN PASIEN DI PUSKESMAS MLATI II - Hermawan, Budi; Sukardi, Sukardi (Jurnal Fokus Manajemen Bisnis, 2015)
The study entitled “Antecedent Factors Determining Patient SatisfactionIn Mlati II Health Center "aims to partially determine the effect andsimultaneous variables of caring, effectiveness on an ongoing basis,appropriateness/worthiness, information, efficiency, effectiveness-food to satisfactionpatients at Mlati II Health Center. The population in this study was inpatientswho use the services of Mlati II Health Center. The sampling technique at this research uses purposive sampling. Data collection techniqueusing interviews and questionnaires. 87 samples were processed from 100respondent. The data analysis method used is linear regression analysismultiple. Testing the variables in this study using the help of the programSPSS 16.0 for windows. By using the method of multiple linear regression can be concludedthat the caring variable does not significantly influence satisfactionpatient. The effectiveness variable on an ongoing basis also has no significant effect.The appropriateness/feasibility variable has no significant effect. Information variablesignificant effect. The efficiency variable has no significant effect. Variablefood-effectiveness has no significant effect. Simultaneously the variable Concern (X1), Effectiveness on an ongoing basis (X2), Appropriateness/Feasibility (X3),Information (X4), Efficiency (X5), Food-Effectiveness (X6) have no effectsignificant on patient satisfaction. The resulting coefficient of determination isequal to 0.008 which means 0.8% can explain the variable Concern (X1), Sustained effectiveness (X2), Appropriateness/Feasibility (X3), Information (X4),Efficiency (X5), food-effectiveness (X6) and patient satisfaction (Y) together, while the remaining 92% is explained by other variables not examined.